2012
DOI: 10.1002/anie.201202277
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Base Coordination to a Disilene

Abstract: SiSi activation: Reversible formation of a donor–acceptor complex between an N‐heterocyclic carbene and a cyclotrisilene with carbon‐based substituents shifts the electron density of the double bond and thus induces strong polarization, as shown by the significantly pyramidal tricoordinate silicon atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0
6

Year Published

2013
2013
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 43 publications
(50 reference statements)
1
46
0
6
Order By: Relevance
“…These results indicate that on the coordination of DMAP, the Si1 À Si2 and Si2 À Si3 bond distances of 1 were elongated (2.286 and 2.244 Å), whereas the Si1 À Si3 bond distance was shortened (2.620 Å). A similar elongation of Si ¼ Si double bonds on the coordination of Lewis bases has been reported by Scheschkewitz et al 26 The frontier orbitals of 1 opt and 1ÁDMAP opt are shown in Fig. 3b,c.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…These results indicate that on the coordination of DMAP, the Si1 À Si2 and Si2 À Si3 bond distances of 1 were elongated (2.286 and 2.244 Å), whereas the Si1 À Si3 bond distance was shortened (2.620 Å). A similar elongation of Si ¼ Si double bonds on the coordination of Lewis bases has been reported by Scheschkewitz et al 26 The frontier orbitals of 1 opt and 1ÁDMAP opt are shown in Fig. 3b,c.…”
supporting
confidence: 84%
“…The endocyclic Si1-Si2 and ARTICLE Si2-Si3 bond distances, 2.2906(6) and 2.2556(6) Å, respectively, are between the typical Si À Si (ca. 2.36 Å) 27 and Si ¼ Si bond distances (2.118-2.289 Å) 31,32 , and close to those of N-heterocyclic carbene-coordinated cyclotrisilene (trisilacyclopropene) (2.2700(5)Å) 26 , indicating a significant double-bond character in Si1 À Si2 and Si2 À Si3 bonds. The geometry around Si2 is considerably pyramidalized with the sum of bond angles around Si2 (except the angles involving Si2 À N1 bond) of 312.63(4)°, whereas that around Si3 is almost planar with the sum of bond angles around Si3 (except the bond angles involving Si1 À Si3 bond), 359.30(4)°.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…16). B. Blom and M. Driess cyclotrisilene with exclusively carbon-based substituents by Scheschkewitz, Jutzi and co-workers [105]. In this instance, salt metathesis of 107 with the lithium disilenide (Trip) 2 Si ¼ Si(Trip)(Li{dme} 2 ) (111) afforded a mixture containing 85% of the cyclotrisilene (112).…”
Section: Shmentioning
confidence: 96%
“…More recently, Scheschkewitz and co-workers reported the synthesis of the first aryl substituted cyclotrisilenes and their reactivity towards N-heterocyclic carbenes. [4]…”
mentioning
confidence: 99%